Goma Yashi at farmers’ doorstep - Singh, A K; Singh, Sanjay; Saroj, P L; Singh, R S (Indian Horticulture, 2019)
Introduction of bael cultivation in Gujarat was a great challenge, where people were least aware about its economic relevance and uses, health benefits and its nutritional significance. The research efforts of scientists of CHES, Godhra, led to the development of three varieties of bael, viz. Goma Yashi, Thar Divya and Thar Neelkanth. All of them are better from earlier developed varieties of bael in terms of tree vigour, yield and quality. They are rich in nutrition, antioxidant and biologically active phyto-chemicals, which add medicinal value. All these are performing well under rainfed areas of Gujarat, Rajasthan, Madhya Pradesh and Maharashtra. Of them, Goma Yashi has become very popular among farmers due to thornless, prolific-bearing habit with very high quality of fruits, and suitability for high-density planting. At present, Goma Yashi alone has occupied nearly 150 ha area in different states. Goma Yashi has also reached in Rajasthan, Karnataka, Tamil Nadu, Madhya Pradesh, Haryana, Punjab, Uttar Pradesh, Jammu and Kashmir and Andhra Pradesh. Various post-harvest products are practically demonstrated to farmers, particularly from Gujarat for adaptaion and for popularization. The outcome of series of studies has considerable impact in changing the general thinking process of stakeholders towards the adoption of developed technologies on bael.